Cranial morphology of Morrinhosuchus luziae (Crocodyliformes, Notosuchia) from the Upper Cretaceous of the Bauru Basin, Brazil. (June 2018) - Iori, Fabiano Vidoi; Marinho, Thiago da Silva; Carvalho, Ismar de Souza; Frare, Luiz Augusto dos Santos
Abstract: Although the type material of Morrinhosuchus luziae (Crocodyliformes, Notosuchia) permitted the diagnosis of a new genus and species, its fragmentary nature prevented a detailed analysis of its cranial anatomy. In this study, we analyzed two new specimens of Morrinhosuchus luziae recovered from the Adamantina Formation (Upper Cretaceous) from Cândido Rodrigues and Monte Alto cities (state of São Paulo, Brazil), in the southeastern portion of the Bauru Basin. One specimen, MPMA 12-0050/07, consists of nearly complete skull and mandible which reveals new data and characters of its cranial morphology. Another, less complete specimen, MPMA 04-0019/15, consists of a rostrum with a partially preserved dentition that include a cingulate tooth crown. The analysis of Morrinhosuchus luziae 's anatomy reinforces its phylogenetic position among the advanced notosuchian, allowing the inference of paleoautoecological proposals, and expanding the taxonomic knowledge of the elusive South American notosuchian.